Isolation and Identification of Swan (Cygnus olor) Digestive Tract Cellulothic Bacteria to Support Fiber Degradation - Muhammad Subhan Bahruddin Rosyidi; Muhammad Ali; Wayan Wariata; Djoko Kisworo; Khairunnisah; Qothrunnada Amira Salma; Muhammad Hipzul Mursyid (Jurnal Penelitian Pendidikan IPA, 2024)
Cellulolytic bacteria are bacteria that produce cellulase enzymes capable of degrading cellulose substrates. This study aimed to isolate and identify as well as measure the cellulase enzyme activity of cellulolytic bacteria isolated from the digestive tract of swans (Cygnus olor) in Mataram. The bacteria were isolated using de Man Rogosa Sharpe (MRS) selective media with the spread plate method. Then, the extracellular enzyme activity test was conducted by growing selected pure isolates on 1% Carboxy Methyl Cellulose (CMC 1%) media, followed by pouring 0.1% congo red solution and rinsing with 1M NaCl solution to determine cellulolytic activity (cellulolytic potential indicated by the appearance of a clear zone around the colony) and measuring the cellulolytic index. The bacterial isolation results obtained 4 isolates with the potential to support fiber degradation in animal feed. The highest cellulolytic index was produced by the isolate coded S1, reaching 34.5 mm, while the lowest cellulolytic index was produced by 2 isolates coded J21 and I2, reaching 18.8 mm.